Take-home examination proctoring technologies: Undergraduate mathematics education students’ perceptions in an open distance learning environment - Tšhegofatšo Phuti Makgakga (Interdisciplinary Journal of Education Research)
Many higher education institutions (HEIs) in both developed and developing countries have migrated to take-home examinations (THEs), which require monitoring, just as traditional venue-based examinations do. The purpose of this existential phenomenological study was to explore undergraduate mathematics education students’ perceptions of the use of remote proctoring during examinations at an open and distance learning institution in South Africa. Perception theory was employed to examine the usefulness and ease of use of technology to guide the study. The interpretive paradigm was used to qualitatively analyse the collected data. Twenty-four undergraduate mathematics education students enrolled in the Teaching Mathematics in FET (TMS3725) module were purposively sampled to respond to an open-ended questionnaire. The data were captured in a table and grouped according to question items. Thematic analysis was conducted to analyse the data collected from the questionnaires. The findings revealed positive perceptions of the usefulness and usability of online proctoring systems. However, negative perceptions related to the drawbacks of using online proctoring systems included students’ reactions to these systems and potential technical problems. It is recommended that students continue attending online proctoring workshop sessions to become familiar with technological software that can be both useful and easy to use during examinations. Additionally, the technical team should continue to provide support to students in using online proctoring systems during examinations.